Socioeconomic Status and Poor Health Outcome at 10 Years of Follow-Up in the Multi-Ethnic Study of Atherosclerosis. - Steven Shea; Joao Lima; Ana Diez-Roux; Neal W Jorgensen; Robyn L McClelland (PLoS ONE)
Background/objectives Predictors of healthy aging have not been well-studied using longitudinal data with demographic, clinical, subclinical, and genetic information. The objective was to identify predictors of poor health outcome at 10 years of follow-up in the Multi-Ethnic Study of Atherosclerosis (MESA). Design Prospective cohort study. Setting Population-based sample from 6 U.S. communities. Participants 4,355 participants In the MESA Study. Measurements Poor health outcome at 10 years of follow-up was defined as having died or having clinical cardiovascular disease, depression, cognitive impairment, chronic obstructive pulmonary disease, or cancer other than non-melanoma skin cancer. Absolute risk regression was used to estimate risk differences in the outcome adjusting for demographic variables, clinical and behavioral risk factors, subclinical cardiovascular disease, and ApoE genotype. Models were weighted to account for selective attrition. Results Mean age at 10 years of follow-up was 69.5 years; 1,480 participants had a poor health outcome, 2,157 participants were in good health, and 718 were unknown. Older age, smoking, not taking a statin, hypertension, diabetes, and higher coronary calcium score were associated with higher probability of poor health outcome. After multivariable adjustment, participants in the lowest income and educational categories had 7 to 14% greater absolute risk of poor health outcome at 10 years of follow-up compared to those in the next highest categories of income or education (P = 0.002 for both). Those in the lowest categories of both income and education had 21% greater absolute risk of poor health outcome compared to those in the highest categories of both income and education. Conclusions Low income and educational level predict poor health outcome at 10 years of follow-up in an aging cohort, independent of clinical and behavioral risk factors and subclinical cardiovascular disease.